A linguistic kaleidoscope of the Malay letter; The case of the eighteenth century official letters from the Sultanate of Buton - Suryadi, S. (Wacana, Journal of the Humanities of Indonesia, 2015)
The Malay letters make up the largest category of documents among the Malay manuscripts preserved at Leiden University Library, the Netherlands. The corpus represents the scope of the territories under Dutch East Indies authority during the colonial era. In fact, they are authentic documents which denote not only political contact between the local kingdoms in the Archipelago (Nusantara) with the Dutch East Indies government in Batavia during colonial times but also constitute an important source for the study of the historical development of the Malay language. This essay looks at the language characters of such letters which came from the court of Buton in Southeast Sulawesi. It aims to sketch the linguistic variety of the classical Malay language represented in its eighteenth century letter-writing tradition. Having specific diction and features that confirm local influences, the language of the letters shows distinctiveness in terms of phonology, morphology and syntax.